Educational proposal to address internal and external factors limiting access to financial credit in women-led enterprises, Cajamarca, Peru - Tarrillo Saldaña, Oscar (2024)
Accessibility to financial credit for women-led enterprises is influenced by a set of internal and external factors. In this context, the principal objective of the study is to develop a educational proposal to address the internal and external factors limiting access to financial credit in companies led by women in Cajamarca, Peru. The study was non-experimental, transversal, of a basic type. The sample comprised 377 companies, the sampling was non-probabilistic for convenience and the technique was the survey. The results reflect the existence of predominant internal factors such as the lack of credit history (70%), the lack of documentation and required information (65%), the high levels of debt (65%) and the lack of financial education to access financing (60%); and, regarding external factors, the most predominant are the excess of requirements (84%), costs associated with maintaining an account (79%) and distrust in the financial system (62%) that make it difficult to take out financial credit. Ultimately, women entrepreneurs in Cajamarca face both internal and external obstacles that negatively impact their ability to access financing. Given this situation, a specific proposal has been developed aimed at overcoming these limitations.